The process by which users become active knowledge contributors in programming‐focused online communities - Nieminen, Henri (2018)
The recent popularity of social knowledge sharing platforms has encouraged people to seek and to share knowledge on them. Motivating users to contribute knowledge has been a major challenge for online communities, in which only a relatively few online knowledge sharing communities have been able to succeed. The goal of the thesis was to find out why users share knowledge, and how users become active knowledge contributors in programming focused online communities. With this information the communities could better identify the users that are likely to become knowledge contributors, and find ways to encourage them to begin contributing knowledge. A qualitative study was carried out to find answers the research problem. Semi-structured interviews were used to collect stories from 18 knowledge contributors on Internet Relay Chat (IRC) network Freenodes programming focused communities. The interviewees were selected based on their activity in knowledge sharing during a selected period of time. Content analysis and narrative analysis were used to analyze the interview data in order to build a process theory. The process theory explains how users become knowledge contributors after initially joining a community. The process theory indicates that users initially join a community to learn more about the topic of the community, to get help with a problem, and to keep up to date with the topic of the community. After joining, the users begin familiarizing themselves with the community by observing or by socializing, and when familiar with the community they start seeking knowledge. Only after the users have gained enough knowledge and confidence in their knowledge do they begin sharing knowledge. The majority of the users were motivated to participate in the online knowledge sharing communities by the possibility to learn. Sharing knowledge was also found to be motivated by learning opportunities. Some users share knowledge in order to validate their knowledge, if they make mistakes someone in the community might correct them.